GERAKAN LITERASI PENDIDIKAN MEMBANGUN GENERASI MILENIAL YANG BERKARAKTER - Abubakar Muhammad Nur (LEMBAGA PENELITIAN PUBLIKASI DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2023)
Abstract The presence of digital technology has influenced the mindset, and behavior of millennials as pioneers of change. The change, colored with various problems that boil down to the decline of the character of the millennial generation. To manage these dynamics, the educational literacy movement, is one of the efforts in forming human resources of character and civility. The purpose of this study is to know the characteristics of millennials in community life in the digital era; and Describe the educational literacy movement to build the capacity of millennials in the era of digital technology that is advanced, characterful and civilized. The method used is qualitatively descriptive. The results of the discussion show that: Millennials like to position themselves in the freedom zone and always dwell on the diameter of the fingers, having a lot of information from various sources that vary. Digital literacy also facilitates millennials in obtaining knowledge and knowledge more easily and quickly. Millennials who always struggle in the digital technology zone based on educational literacy, can have competence, skills and skills to think critically, creatively, communicatively, insights and productive thinking paradigms, and have a civilized character